The border between French Sudan (Mali) and Guinea : from an intra-imperial boundary to an inter-state border (1878-1956) - (:unkn) unknown (My University, 2019)
"The two lungs of one and the same body" is a metaphor commonly used to refer to the states of Mali and Guinea, indicating the absurd and arbitrary nature of their separation. Their common border is a 858-kilometer long line, inherited from the administrative boundary between two colonies of French West Africa. Though never clearly demarcated nor actually materialized, it stems from the territorial division of French West Africa, the purpose of which was simply to create manageable geographical units, not future states. This thesis proposes to consider the border between Mali and Guinea (former French Sudan) in its entirety, from the territorial conquest initiated by the French in 1878, up to 1956 with the establishment of autonomous territories within the AOF (French West Africa). It proposes to write its history: its construction and then administration by the French but, above all, the story of its appropriation by the communities which live in the border territories. Analysing the populations' trans-territorial habits and the forms of exploitation of the imposed spatial framework enables us to grasp its historicity, to gradually erase the phantom nature of this line and imagine the processes of spatial appropriation from the bottom up and how this helped generate new identities and caused the border to take root on the eve of the upheavals of independence.
Keywords: African Research